2022
DOI: 10.3389/fmicb.2022.846747
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Effect of Selenomethionine on Porcine Deltacoronavirus in Pig Kidney Epithelial Cells

Abstract: Porcine deltacoronavirus (PDCoV) is an emerging porcine intestinal coronavirus in recent years, which mainly causes different degrees of vomiting and diarrhea in piglets and has caused great harm to the swine husbandry worldwide since its report. Selenium is an essential trace element for organisms and has been demonstrated to have antiviral effects. In this study, pig kidney epithelial (LLC-PK) cells were used to study the antiviral activity of selenomethionine (Se-Met) (2, 4, 8, and 16 μM) against PDCoV by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In Madin-Darby Canine Kidney (MDCK) cells, modified SeNPs inhibit the H1N1 influenza virus and Caspase 3-mediated apoptosis caused by virus infection ( 52 , 53 ). Our previous research found that selenomethionine (Se-Met) inhibited PDCoV replication on LLC-PK cells ( 29 ). However, most of the above studies are on inorganic and organic selenium, and there are few studies on the antiviral effects of SeNPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Madin-Darby Canine Kidney (MDCK) cells, modified SeNPs inhibit the H1N1 influenza virus and Caspase 3-mediated apoptosis caused by virus infection ( 52 , 53 ). Our previous research found that selenomethionine (Se-Met) inhibited PDCoV replication on LLC-PK cells ( 29 ). However, most of the above studies are on inorganic and organic selenium, and there are few studies on the antiviral effects of SeNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Serum selenium levels are linked to the prognosis of Corona Virus Disease 2019 (COVID-19), and higher serum selenium levels are related to a higher cure rate ( 28 ). In a previous study by our group, it was discovered that Se-Met inhibited PDCoV replication in vitro , and selenium could alleviate the viral infection-induced oxidative stress, and increased the levels of various cytokines in host cells, boosting the level of cellular immunity to inhibit virus replication ( 29 ). To sum up, selenium may be a promising drug for treating COVID-19 and other virus infections, allowing for the development of new and highly effective antiviral drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In a different type of mechanism, selenizing astragalus polysaccharide can activate the PI3K/AKT pathway to inhibit autophagy, thereby preventing PCV2 from replicating as a result of oxidative stress (190). In other investigations, SeMet at doses higher than physiological (16 µM) inhibited the replication of porcine delta coronavirus in pig kidney epithelial (LLC-PK) cells (191). Finally, supplementing diets with Se was found to reduce virus shedding and improved ISG and IFN expression.…”
Section: Role Of Se In Livestock Virus Infection and Enhancing Immune...mentioning
confidence: 95%
“…The anti-PDCoV effect of RDV in other cells and in vivo also needs to be validated. The inhibition of PDCoV by selenomethionine is related to its enhancement of cellular immunity (such as the upregulation of MAVS expression, IRF3 phosphorylation and IFN-α/β production) and antioxidant capacity (such as increased GSH-PX activity and SOD content and decreased H 2 O 2 content) [ 94 ]. Griffithsin restricts PDCoV attachment and internalization by binding to S protein [ 86 ].…”
Section: Bioactive Compounds With Anti-pecov Activitymentioning
confidence: 99%